Analysis of living habit risk factors for esophageal cancer in central China: A bi-center case-control study - Yuan, Lingzhi; Shen, Peijun; Zheng, Shaopeng; Wu, Dongwen; Li, Xinmeng; Cai, Ting; Yao, Yao; Song, Yunhe; Wang, Fen (Frontiers in Oncology, 2023)
Background: Esophageal cancer remains a public health problem in many countries, especially developing countries. The early lifestyle preventive measures mentioned in the treatment guidelines for esophageal cancer are very limited. We aimed to evaluate the risk factors for esophageal cancer in a high-incidence area in China and to provide evidence for clinical intervention in esophageal cancer prevention. Methods: Symptom and lifestyle/habit questionnaires including 19 items were designed. The correlation between the occurrence of esophageal cancer and living habits was analyzed retrospectively through questionnaire survey. A total of 708 subjects (365 esophageal cancer, 343 non-esophageal cancer) enrolled from two hospitals in central China (Linzhou Esophageal Cancer Hospital and The Third Xiangya Hospital of Central South University) completed symptom and lifestyle/habit questionnaires. We used conditional logistic regression to estimate the odds ratio (OR) with consideration of 95% confidence interval (CI). Results: The composition ratio analysis showed that the top five lifestyle factors related to esophageal cancer were eating too fast, drinking, hot drinks, smoking and overeating. Univariate analysis showed that 15 factors, including male sex, smoking, drinking, eating too fast, overeating, hot drinks, greasy food, acidic food, hard food, strong tea, coffee, bedtime immediately after meals, eating food before bedtime, difficult defecation, and an overtight belt, were associated with esophageal cancer (all P <0.05). Logistic multivariate regression analysis showed, drinking (OR 3.609, 95%CI 2.223-5.859; P=0.000); hot drinks (OR 2.672, 95%CI 1.786-3.997; P=0.000); overeating (OR 2.110, 95%CI 1.411-3.154; P=0.000); eating too fast (OR 1.879, 95%CI 1.274-2.772; P=0.001); strong tea (OR 1.882, 95%CI 1.171~3.023; P=0.009); hard food (OR 1.723, 95%CI 1.113-2.667; P=0.015); smoking (OR 1.686, 95%CI 1.045-2.720; P=0.032), which were significantly associated with the development of esophageal cancer. Conclusion: The unhealthy lifestyles of patients in high-incidence areas of esophageal cancer in central China are significantly associated with the incidence of esophageal cancer. Lifestyle changes that address these factors, especially overeating and eating too fast, which are rarely studied or discussed despite being common, may improve esophageal cancer management and treatment outcomes. The present results may be used as a reference for preventive education and treatment.